Evaluation of MODIS Albedo Product over Ice Caps in Iceland and Impact of Volcanic Eruptions on Their Albedo - Simon Gascoin; Sverrir Guðmundsson; Guðfinna Aðalgeirsdóttir; Finnur Pálsson; Louise Schmidt; Etienne Berthier; Helgi Björnsson (Remote Sensing, 2017)
Albedo is a key variable in the response of glaciers to climate. In Iceland, large albedo variations of the ice caps may be caused by the deposition of volcanic ash (tephra). Sparse in situ measurements are insufficient to characterize the spatial variation of albedo over the ice caps due to their large size. Here we evaluated the latest MCD43 MODIS albedo product (collection 6) to monitor albedo changes over the Icelandic ice caps using albedo measurements from ten automatic weather stations on Vatnajökull and Langjökull. Furthermore, we examined the influence of the albedo variability within MODIS pixels by comparing the results with a collection of Landsat scenes. The results indicate a good ability of the MODIS product to characterize the seasonal and interannual albedo changes with correlation coefficients ranging from 0.47 to 0.90 (median 0.84) and small biases ranging from −0.07 to 0.09. The root-mean square errors (RMSE) ranging from 0.08 to 0.21, are larger than that from previous studies, but we did not discard the retrievals flagged as bad quality to maximize the amount of observations given the frequent cloud obstruction in Iceland. We found a positive but non-significant relationship between the RMSE and the subpixel variability as indicated by the standard deviation of the Landsat albedo within a MODIS pixel (R = 0.48). The summer albedo maps and time series computed from the MODIS product show that the albedo decreased significantly after the 2010 Eyjafjallajökull and 2011 Grímsvötn eruptions on all the main ice caps except the northernmost Drangajökull. A strong reduction of the summer albedo by up to 0.6 is observed over large regions of the accumulation areas. These data can be assimilated in an energy and mass balance model to better understand the relative influence of the volcanic and climate forcing to the ongoing mass losses of Icelandic ice caps.